Clinical Outcome of Implant Placement with Xenograft Augmentation - Varraveethrachodt, Nichapa; Kumchai, Thongnard; Chantravekin, Yosananda (Khon Kaen University Dental Journal, 2025)
Objective: Exposed implant threads with good primary stability are common condition in implant dentistry practice. This issue is usually corrected with various types of bone substitutes, including xenografts. However, many complications, such as graft displacement and foreign body reaction, have been reported. The objective of the study was to evaluate clinical and radiographic outcomes, as well as the patient-reported outcome measures (PROM) of patients receiving implant placement with xenograft augmentation. Materials and Methods: The patients who received implant placement with xenograft augmentation at Dental Implant Clinic, Faculty of Dentistry, Bangkokthonburi University, over 6 to 12-month period were included in this study. Clinical examinations were performed and PROM Functional and Esthetic Questionnaires were used to evaluate the clinical outcomes. Cone beam CT was also used to evaluate surrounding bone volume three-dimensionally. The percentage of bone gain was calculated using adjacent tooth’s cemento-enamel junction as reference point. Descriptive statistics were used to demonstrate all data. Results: For the results, from clinical evaluation, all 36 implants in 18 patients were clinically successful with no mobility, symptom or history of infection. From PROM evaluation, 94.4% of patient could intake regular food, whereas 33.3% had problems about food impaction. All of patients were satisfied in the esthetic outcomes. Radiographic evaluation showed that the percentages of bone gain at the buccal, mesial and distal aspects were 45.4 ± 17.6%, 37.4 ± 19.5% and 35.9 ± 16.4%, respectively. Conclusion: For conclusion, during the short follow-up period, good clinical, PROM and radiographic outcomes were achieved with implant placement combined with xenograft augmentation. The results are consistent with previous short-term studies. Compared with other bone substitutes, xenografts have low turn-over rate property which lead to stable bone levels, as well as good functional and esthetic outcomes. However, long-term follow up is suggested in this group of patients.